Masculine scenarios - Alizade, Alcira Mariam (Psychoanalysis & women series., 2003)
'Human identity, sexual identity, primary and secondary identification, object choice, narcissism - all of these lie on a continuum with homosexuality, transsexualism, transvestism, heterosexuality and asexuality. Concepts on sexuality and gender are outlined anew in an interplay of theoretical and clinical networks, with the aim of increasing the efficiency of analytic praxis freed from prejudice and monolithic convention.' Alcira Mariam Alizade from the Foreword.